2021
DOI: 10.1093/europace/euab116.221
|View full text |Cite
|
Sign up to set email alerts
|

ProGlide venous closure device facilitates early ambulation following cryoablation of atrial fibrillation

Abstract: Funding Acknowledgements Type of funding sources: Foundation. Main funding source(s): Heart Foundation Background Same-day discharge following atrial fibrillation (AF) ablation is increasingly common. ProGlide device suture-mediated vascular closure (PD) offers a technique that may expedite mobilisation following large-bore (>12F) venous access. The utility of PD closure following cryoablation of AF has not been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…In another retrospective study by Mohamed et al, 8 the Perclose ProGlide device was associated with shorter median length of stay than manual compression or a figure‐of‐eight suture (Perclose ProGlide 27.5 h, manual compression 29 h, figure‐of‐eight suture 29 h; p = .003), although this did not impact on same‐day discharge rates. These findings are similar to those in an analysis by Wong et al which found no difference in same‐day discharge rates in patients undergoing AF cryoablation receiving a figure‐of‐eight suture or Perclose Proglide (respectively, same‐day discharge rates of 73% vs. 81%; p = .386) 12 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In another retrospective study by Mohamed et al, 8 the Perclose ProGlide device was associated with shorter median length of stay than manual compression or a figure‐of‐eight suture (Perclose ProGlide 27.5 h, manual compression 29 h, figure‐of‐eight suture 29 h; p = .003), although this did not impact on same‐day discharge rates. These findings are similar to those in an analysis by Wong et al which found no difference in same‐day discharge rates in patients undergoing AF cryoablation receiving a figure‐of‐eight suture or Perclose Proglide (respectively, same‐day discharge rates of 73% vs. 81%; p = .386) 12 …”
Section: Discussionsupporting
confidence: 89%
“…6 In another retrospective study by Mohamed et al, 8 (respectively, same-day discharge rates of 73% vs. 81%; p = .386). 12…”
Section: E N T R a L I L L U S T R A T I O Nmentioning
confidence: 99%